Rumah Sakit Hewan Di Kebun Binatang Kasang Kulim Dengan Pendekatan Arsitektur Tropis - Redito Pernandes; Wahyu Hidayat; Mira Dharma S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In Kasang Kulim zoo there are so many animals less of health attention. The cause of this problem is because there is no Animal Hospital Facilities (AHF) in this zoo. This is the reason why Animal Hospital is needed to fulfill health requirements in this zoo. The purposes of this research are to identify the supporting facilities needed, describing the characteristics of tropical architecture into the design of Animal Hospital, and formulating the concept into the design of Animal Hospital in Kasang Kulim Zoo. The methods of presenting the Animal Hospital design are through concept, zoning, mass order, outdoor planning, mass formation, indoor planning, structure, utilitiy, building facade, and design result. The research approach is applying the principle of tropical architecture. The tropical architecture principles applied are responsive to the environment and combined with the design concept, Garden Hospital. In this design, the building is divided into two building. The first is Animal Hospital building which is intended for pets, and second one is Animal Health Center which is intended for animals in Kasang Kulim Zoo. The combination between the concept and theme will be the characteristic from this design, that is every existed room will get natural lighting and air sirculation.Keywords: Animal Hospital, Tropical Architecture, Garden Hospital.